Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1987
DOI: 10.1016/0014-5793(87)80518-5
|View full text |Cite
|
Sign up to set email alerts
|

Differential regulation of muscle acetylcholine receptor γ‐and ϵ‐subunit mRNAs

Abstract: The contents of the mRNAs encoding the y-and E-subunits of the nicotinic acetylcholine receptor as well as the single-channel properties of the receptor have been assessed in innervated, denervated and reinnervated rat muscle. The changes in abundance of the ),-and E-subunit mRNAs correlate with the changes in relative density of two classes of acetylcholine receptor channels. The results support the view that a switch in the relative abundance of the y-and E-subunit mRNAs is a major mechanism in regulating th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
101
1
1

Year Published

1989
1989
2007
2007

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 193 publications
(122 citation statements)
references
References 33 publications
10
101
1
1
Order By: Relevance
“…Triceps muscles from adult Wistar rats (150-300 g) or rats of various postnatal ages, killed with ether, CO2 or decapitated were removed and immediately frozen in liquid nitrogen, Denervation and reinnervation experiments were performed as described previously [12], Pharmacological muscle inactivation was induced either by injection of botulinum toxin (BoTX) type A into the triceps muscle or by chronic blockade of nerve signal conduction in the sciatic nerve usmg tetrodotoxin (TTX) following procedures described by Brenner et el. [13] [16] to Biodyne membranes (Pall) and crosslinked with the UV Stratalinker from Stratagene.…”
Section: 1 Isolation and Surgery Of Rat Musclementioning
confidence: 99%
See 2 more Smart Citations
“…Triceps muscles from adult Wistar rats (150-300 g) or rats of various postnatal ages, killed with ether, CO2 or decapitated were removed and immediately frozen in liquid nitrogen, Denervation and reinnervation experiments were performed as described previously [12], Pharmacological muscle inactivation was induced either by injection of botulinum toxin (BoTX) type A into the triceps muscle or by chronic blockade of nerve signal conduction in the sciatic nerve usmg tetrodotoxin (TTX) following procedures described by Brenner et el. [13] [16] to Biodyne membranes (Pall) and crosslinked with the UV Stratalinker from Stratagene.…”
Section: 1 Isolation and Surgery Of Rat Musclementioning
confidence: 99%
“…rated muscle and from muscle denervated for 7 days and subjected to RNA hybridization analysis. Reinnervation e×periments were performed on rat diaphragm where functional reinnervation lind been followed in,parallel on separate muscle preparations [12]. N and D indicate normal and denervated muscle.…”
Section: Innervation Of Muscle Down-regulates Mrna Levels Of Myod Andmentioning
confidence: 99%
See 1 more Smart Citation
“…The levels of the ,d-and fsubunit mRNAs both increase transiently with the increase being much more marked for the esubunit mRNA. The rapid increase of f-subunit mRNA and concomitant decrease of y-subunit mRNA levels is of particular interest, since a correlation between the expression of adult type end-plate channels and the abundance of e-subunit mRNA was previously found [2,3]. To investigate the relationship between the time course of changes in the level of the y-and e-subunit mRNAs and the conversion of channel properties, we analyzed the developmental changes of these mRNAs with a finer time resolu- Days tion.…”
Section: Densitometric Evaluation Of Autoradiogramsmentioning
confidence: 99%
“…In the adult form of the receptor an e-subunit substitutes the ~,-subunit. Der~ervation results in a large increase of newly synthesized AChEs, incorporated mostly into the extrajunctional plasma membrane, which have biophysical and biochemical properties distinct from those of junctional AChRs [5]. Northern blot hybridization experiments have shown that the expression of the ~,-and e-subunits correlates with the presence of the extrajunctional and junctional forms of the receptor respectively, suggesting that the exchange of a single subunit can account for the different properties observed after denervation of during development [5,6].…”
Section: ! Introductionmentioning
confidence: 99%